In the development nexus of everyday violence and justice system reform: a comparative study of the United Nations and International Justice Mission approaches to law enforcement and judicial capacity building - Javier, Armi (2020)
The purpose of this study is to draw attention to the crossroads of everyday violence in developing countries and examine justice reform as a means to address the phenomenons of forced labor, sex trafficking and other forms of everyday violence affecting the vulnerable. It takes a look at the present state of justice system reform efforts through the comparative study done of International Justice Mission and the United Nations in their crime prevention programs. Questions regarding their implementation approaches, efficacies and outcomes are studied in order to assess what is working and what is not in this quest to protect the vulnerable from lawlessness and impunity by the building up of broken justice systems.